A real time impact evaluation of the Dr. Lee Jong-Wook - Seoul project in Lao PDR: Final Report - Kim, Tae Jong; Kim, Jungho; Lee, Kye Woo (A real time impact evaluation of the Dr. Lee Jong-Wook - Seoul project in Lao PDR: Final Report, 2016)
1. The Dr. LEE Jong-Wook—Seoul Project in Lao PDR is an ambitious development cooperation initiative funded by the Korea Foundation for International Healthcare (KOFIH) in 2010. Through this project the Lao University of Health Sciences (UHS) and the Seoul National University College of Medicine (SNUCM) are collaborating to upgrade the medical education capacity of the UHS faculty members. The ultimate objective of the project is to contribute to the overall improvement of the Lao people’s health. The project in its current stage is a fiveyear collaboration with a plan in place to extend the program period to a total of nine years. Fully implemented, the project envisions retraining of about 80 of the 300 UHS professors at the SNUCM. The project also includes provisions to dispatch faculty advisors from SNUCM, and provide equipment and devices for education and research at the UHS. 2. The Impact Evaluation Lab of the KDI School of Public Policy and Management has been carrying out an evaluation study on the Dr. LEE Jong-Wook—Seoul Project since 2011 in collaboration with the partnering institutions and agencies both in Lao PDR and Korea; the UHS, the Lao Ministry of Health, the SNUCM, and the KOFIH. This volume is the final report of the collaborative efforts for assessment. 3. The collaboration has two main objectives: impact evaluation and real-time feedback to the partnering institutions and agencies. Given the three-year timeframe for the study, the impact evaluation team chose to focus on a series of intermediate outcome rather than the ultimate goal of improving Lao people’s health. They are: learning outcomes for the UHS faculty members participating in the one-year exchange program at the SNUCM; the learning outcomes of the UHS students; and finally, improvements in the clinical practices of the young physicians upon their graduation from UHS. The first of these is to be monitored and assessed by the UHS and the SNUCM. The KDI School’s Impact Evaluation Lab is to focus on the latter two measures. 4. For the students’ learning outcome measurement, the evaluation team employs the test battery developed and maintained by the Medical Education Assessment Consortium (MEAC) of Korea. The questions in the test, designed to assess the test-takers’ mastery of medical science and clinical knowledge, have been translated into Lao. In addition, the academic achievement scores at UHS (i.e., grade point average, or GPA) are also used to supplement the MEAC scores. For measuring the young physicians’ clinical practices, we utilize Disease Treatment Committee (DTC) data collected by each central and provincial hospital in Lao. DTC data are composed of two sets of indicators: the Standard Treatment Guidelines (STGs) and the Reasonable Use of Drugs (RUD) guidelines. Baseline and two rounds of follow-up studies have been carried out to collect information on UHS student learning using the MEAC test battery, and physician practices using the DTC data from 2011, 2012 and 2014. 5. Thus, the impact evaluation strategy will compare the changes in the students’ learning outcome measures over the years between the treatment and control groups. The treatment group consists of medical subjects or fields taught by the UHS faculty members returning from Seoul, and the control groups represent other subjects or fields. Note that the treatment or control group is not a clearcut due to the integrated curriculum. That is, a subject or a field in medicine is taught by a group of lecturers rather than one. In the analysis, the scale of intervention for a subject or a field is measured by the share of the Dr. LEE JongWook—Seoul Project participants in total teaching team members and total team teaching hours.